2016 IEEE International Energy Conference (ENERGYCON) 2016
DOI: 10.1109/energycon.2016.7514026
|View full text |Cite
|
Sign up to set email alerts
|

On the evaluation of plug-in electric vehicle data of a campus charging network

Abstract: Abstract-The mass adoption of plug-in electric vehicles (PEVs) requires the deployment of public charging stations. Such facilities are expected to employ distributed generation and storage units to reduce the stress on the grid and boost sustainable transportation. While prior work has made considerable progress in deriving insights for understanding the adverse impacts of PEV chargings and how to alleviate them, a critical issue that affects the accuracy is the lack of real world PEV data. As the dynamics an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Table IV presents the input parameters of the BEVs, resulting from their respective probability distributions. We can deduce from these results that average energy demand amounts to 17.65 kWh, more than double the average demand according to [21]. Furthermore, we impose identical dynamic tariffs on…”
Section: Price Mechanismmentioning
confidence: 87%
See 2 more Smart Citations
“…Table IV presents the input parameters of the BEVs, resulting from their respective probability distributions. We can deduce from these results that average energy demand amounts to 17.65 kWh, more than double the average demand according to [21]. Furthermore, we impose identical dynamic tariffs on…”
Section: Price Mechanismmentioning
confidence: 87%
“…The long time for which BEVs are parked at the workplace offers the possibility to charge these with locally produced PV energy. However, a recent study showed that the average energy transfer at the workplace is 8.53 kWh [21]. Since a 10 kW charger can transfer up to 80 kWh of energy to a BEV during an 8 hour workday, we can conclude that the charger will likely not be fully utilized, which in turn reduces the economic performance of the system.…”
Section: B Contributionsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, considering the widespread adoption of EVs, the uptake of EVs depends more on charging access placement in the community and working place, rather than public recharging stations [40][41][42]. Second, the research showed that consumer perception of EVs could be a significant barrier to its market penetration [43,44]; however, if consumers can obtain knowledge accurately and experience electric vehicles regularly, the attitudes and willingness toward these types of vehicles will increase significantly. Furthermore, it revealed that EV car manufacturers and governments should further promote the advantages related to EV technology.…”
Section: Discussionmentioning
confidence: 99%
“…13 For example, Birnie, 14 Mouli et al, 15 and Tulpule et al 16 examined the feasibility of using solar PV systems installed on workplaces to charge private-owned EVs. Chowdhury et al, 17 Bayram et al, 18 Esfandyari et al, 19 and Ahmad and Alam 20 investigated the implications for plug-in EVs and renewable energy sources integrated at university campuses. There are studies addressing citywide data to analyze the charging behavior of private EVs owners.…”
Section: Introductionmentioning
confidence: 99%